(untitled) (Fiep Bulletin - online, 2015)
The aging populacional folloied of the longevity added the chronic-degenerative not transmissible illnesses that follow the aged one, has presented one part of aged with chronic pain. This pain can intervene with the realization of the activities of the daily life being able to cause functional limitation, with consequent interference in the functional capacity of these aged ones. In this perspective, this study of descriptive exploratório character with transversal delineation it aimed at to investigate the prevalence, incidence and to characterize the pain in 27 aged that participate of groups of third age in the city of Jequié - BA. The majority of the aged ones was woman, with prevalence of pain in 100% of the searched ones, being that 77.7% had above 6 months before. The localizations most frequent had been the lumbar column (44.4%), right shoulder/superior thorax and knee (29.6%). The cited illnesses had been artrose (16.3%) and discal hernia (7.2%). The intensity of numerical pain scale varied of 2 to 10 points, being told as unbearable (58.3%), severe (29.8%) and moderate (11.9%).